Government and Growth - Milad Zarin-Nejadan (University of Neuchâtel, Institute of Economic Research (IRENE), 2011)
The relative size of the State in industrialized economies has increased dramatically during the past century giving rise to legitimate fears that such a trend might end up having an adverse impact on growth. This paper explores the relationship between the development of government activities and economic growth. It starts by evoking problems related to the measurement of the public sector before reviewing statistical evidence on the long-term growth of the share of the State in the economy. It then provides a number of explanations for this phenomenon including those pertaining to the functioning of the political system itself thereby pointing towards inefficiencies. The next step is to explore the principal avenues along which government interventions can positively or negatively interfere with the growth potential of the economy. It turns out that while public expenditures – especially those responding to market failures – tend to be favorable to growth, most taxes are growth-hindering. The final part of the paper singles out some pitfalls in the empirical investigation of this relationship. The conjecture is that the nonlinear and possibly endogenous nature of the hypothesized nexus can explain the lack of consensus in empirical studies conducted so far.
Keywords: E62; H11; H21; H50; O40; 330; Government growth; Public expenditure; Taxes; Economic growth; Endogenous growth